Serologic Responses to Recombinant Pneumocystis jirovecii Major Surface Glycoprotein among Ugandan Patients with Respiratory Symptoms - Blount, Robert J.; Jarlsberg, Leah G.; Daly, Kieran R.; Worodria, William; Davis, J. Lucian; Cattamanchi, Adithya; Djawe, Kpandja; Andama, Alfred; Koch, Judith; Walzer, Peter D.; Huang, Laurence (PloS one, 2012)
Little is known about the serologic responses to Pneumocystis jirovecii major surface glycoprotein (Msg) antigen in African cohorts, or the IgM responses to Msg in HIV-positive and HIV-negative persons with respiratory symptoms. We conducted a prospective study of 550 patients, both HIV-positive (n = 467) and HIV-negative (n = 83), hospitalized with cough ≥2 weeks in Kampala, Uganda, to evaluate the association between HIV status, CD4 cell count, and other clinical predictors and antibody responses to P. jirovecii. We utilized ELISA to measure the IgM and IgG serologic responses to three overlapping recombinant fragments that span the P. jirovecii major surface glycoprotein: MsgA (amino terminus), MsgB (middle portion) and MsgC1 (carboxyl terminus), and to three variations of MsgC1 (MsgC3, MsgC8 and MsgC9). HIV-positive patients demonstrated significantly lower IgM antibody responses to MsgC1, MsgC3, MsgC8 and MsgC9 compared to HIV-negative patients. We found the same pattern of low IgM antibody responses to MsgC1, MsgC3, MsgC8 and MsgC9 among HIV-positive patients with a CD4 cell count <200 cells/µl compared to those with a CD4 cell count ≥200 cells/µl. HIV-positive patients on PCP prophylaxis had significantly lower IgM responses to MsgC3 and MsgC9, and lower IgG responses to MsgA, MsgC1, MsgC3, and MsgC8. In contrast, cigarette smoking was associated with increased IgM antibody responses to MsgC1 and MsgC3 but was not associated with IgG responses. We evaluated IgM and IgG as predictors of mortality. Lower IgM responses to MsgC3 and MsgC8 were both associated with increased in-hospital mortality. HIV infection and degree of immunosuppression are associated with reduced IgM responses to Msg. In addition, low IgM responses to MsgC3 and MsgC8 are associated with increased mortality.